2019
DOI: 10.1002/jssc.201900346
|View full text |Cite
|
Sign up to set email alerts
|

Salinity and pH as factors affecting the passive sampling and extraction of pharmaceuticals from water

Abstract: Passive sampling is an attractive technique for the long‐term monitoring of pharmaceuticals in the water environment. The reliability of the received results depends on the properly performed calibration, namely the determination of analyte sampling rates. This step can be the source of a systematic error, as the sampling rate values are dependent on the water donor phase parameters. This is especially important for pharmaceuticals, since their chemical characteristics and ionic form change with pH. In this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…Similar results were also obtained for organophosphate flame retardants (OPFRs) by Yang et al, who reported that the calculated R s values for the neutral molecules exhibited a slight variation in the pH range from 3 to 9 [72]. Therefore, due to differences in charge and physicochemical properties of the various species of a given compound, their uptake into passive sampler might differ significantly, resulting in the diverse pH dependence of the R s for various compounds [31].…”
Section: Phsupporting
confidence: 81%
See 1 more Smart Citation
“…Similar results were also obtained for organophosphate flame retardants (OPFRs) by Yang et al, who reported that the calculated R s values for the neutral molecules exhibited a slight variation in the pH range from 3 to 9 [72]. Therefore, due to differences in charge and physicochemical properties of the various species of a given compound, their uptake into passive sampler might differ significantly, resulting in the diverse pH dependence of the R s for various compounds [31].…”
Section: Phsupporting
confidence: 81%
“…It has been reported that the R s values would not be affected by analyte concentrations in water, however, this is totally dependent on a range of environment factors, such as water turbulence, temperature, salinity, biofouling, physicochemical parameters of water body, and so on [16,[27][28][29][30]. For example, Yabuki et al [27] reported that the R s values increased with temperature, flow rate, and pH, while Shi et al and others [21,[31][32][33] only observed a significant effect of the salinity on uptakes for basic pharmaceuticals. As a matter of fact, these environment conditions are so complex that questions still remain in these aspects as to how the R s values are impacted by environmental factors and how the in situ calibration methods of the R s need to be improved for accurate quantification of target pollutants.…”
Section: Theory Of the Pocismentioning
confidence: 99%
“…Namely, the aqueous phase is mixed during the experiment, most often by means of a magnetic stirrer. Such calibration methods are called quasi-static or semi-static (Caban et al 2016;Jakubus et al 2016;Męczykowska et al 2017a;Lotufo et al 2018;Lis et al 2019).…”
Section: Calibration Of Passive Samplersmentioning
confidence: 99%
“…There are four limiting layers: the receiving phase, membranes, possible biotic contamination of the membrane and the aqueous boundary layer (Ibrahim et al 2013;Vallejo et al 2013;Berho et al 2017). In addition, the R s values may also depend on environmental conditions such as water salinity (Togola and Budzinski 2007;Bayen et al 2014;Męczykowska et al 2018), pH of the donor phase (Li et al 2011(Li et al , 2016aLis et al 2019), temperature (Ibrahim et al 2013;Yabuki et al 2016) and dissolved organic matter concentration (Li et al 2011;Ibrahim et al 2013). For this reason, many scientists propose to use performance reference compounds to make the obtained R s values more reliable.…”
Section: Calibration Of Passive Samplersmentioning
confidence: 99%